Konstruksi Makna Sosial-Religius dan Pandangan Dunia dalam Novel Aulād Ḥāratinā Karya Najib Mahfouz: Kajian Strukturalisme Genetik Lucien Goldmann - Navarro, Mochamad Arvin; Akmaliyah, Akmaliyah; Ridho, Mohammad Rosyid (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2026)
This study examines Aulād Ḥāratinā by Najib Mahfouz through Lucien Goldmann’s Genetic Structuralism to reveal the socio-religious meanings and the author’s worldview reflected in the narrative structure. The study of modern Arabic literature is significant as literary works function not only as aesthetic expressions but also as reflections of social and ideological dynamics within society. Previous studies have largely focused on the novel’s religious allegory, while analyses connecting narrative structure with the author’s collective consciousness remain limited. This research employs a descriptive qualitative method using close reading techniques of the novel text. The findings show that the narrative structure constructs socio-religious meanings through recurring conflict patterns representing the evolution of human values, while the author’s worldview reflects a critical perspective on moral cycles, power structures, and modernity. This study contributes to modern Arabic literary studies by demonstrating that literary works can be understood as reflections of social consciousness as well as critical responses to historical realities.